The truth and opinions of social media users about criminal cases in Argentina - Pérez, María Florencia (Scientific journal of social studies, 2024)
From an analysis of three articles of great importance written by Friedrich Nietzsche, Michel Foucault and Rubén H. Pardo refers to each author’s conception and evolution of the truth and how it is reached. The purpose of comparing these and integrating the thought of current society in general and which is the actual conception of truth that this one has in a context of social media feedback on cases related to criminal law and with great relevance to all Argentinian nation during the year 2023 in Facebook and Instagram. From this study, It will be proved that current society uses social punishment as a means to get to its truth regardless of criminal justice actions, being communication media and social media is are very relevant and influential factor in opinion formers. Likewise, the high level of aggressiveness towards users whose comments differ from a majority-accepted opinion will be denoted, giving rise to the production of a "binomial" made up of two opposite sets of opinions and their punishment towards those users who do not conform to the dominant position, showing impunity of expression behind a device or keyboard.